Enhanced Learning Continuity Framework Using Online Teaching as Alternative Delivery Modality - Hermosisima, Mary Chandra R.; Mobo, Froilan D.; Cutillas, Anesito L. (Future Science / FSH-PH Publications, 2023)
This study explores the integration of technology platforms in online modular learning and proposes an enhanced learning continuity framework using online teaching as an alternative delivery modality. The study captures participants’ experiences related to online modular education through surveys by employing a qualitative approach. The findings demonstrate that integrating technological platforms enhances learning continuity. Online teaching offers flexible and accessible learning experiences, fostering effective teaching and learning. The study emphasizes the significance of comprehensive technical infrastructure, blended learning approaches, pedagogical and learner support services, continuous assessment, and a healthy learning environment in crafting the framework. The framework emphasizes robust technological infrastructure, training programs, blended learning approaches, pedagogical support, diverse assessment strategies, and a healthy learning environment by addressing challenges like the digital divide, technical difficulties, and lack of face-to-face interaction, flexibility, adaptability, and continuous evaluation are emphasized to address specific institutional and learner needs. Implementing the framework requires collaboration among educational institutions, policymakers, and communities to create inclusive online learning environments. Efforts should be made to ensure equitable access to reliable internet connections, support disadvantaged learners, and foster creativity through interactive activities. Monitoring and evaluation play a vital role in tracking progress and making informed decisions for improvement. This study provides a foundation for institutions to develop an enhanced learning continuity framework using online teaching. By optimizing the benefits of online modular learning while addressing challenges, the framework promotes effective teaching and learning in the online education landscape.